Economic incentives and energy production from forest biomass in Argentina - Olemberg, Demián Jeremías (2020)
Argentina faces a double challenge: on the one side, to support and strengthen the economic development process with the enlargement and enhancement of the energy matrix; and on the other side, the country adhered to the global trend of stimulating the development of renewable energies. It is there where the potential of non-conventional renewable energy (NCRE) especially stands out, and dendroenergy in particular. In order to stimulate bioenergy production from ad hoc forest plantations as well as by using forest by-products, it is essential to have a distributed generation regulatory and operational framework, or otherwise to work on a logistic profile that matches supply and demand (industrial and household) for energy, also considering power generation as well as preferrably cogeneration schemes. From a regulatory point of view, Argentina is already on its way towards such a system. The second item implies deeper planning policies, in a longer term. Even though a dynamic NCRE development has been seen for the past few years, dendroenergy projects in particular are below the identified potential. Drawing mainly on the INTA-FAO-Probiomasa consultancy (FAO, 2020a) precedent, this work discusses the identified areas with the greatest dendroenergy potential, the current institutional and regulatory incentives, and the necessary economic requirements for dendroenergy capacity growth.